REPRESENTASI KOMUNIKASI SARKASME DAN SATIRE TERHADAP WARISAN DALAM FILM GARA GARA WARISAN (ANALISIS SEMIOTIKA ROLAND BARTHES) - Cita Auliana (2023)
This study aims to discuss the language of satire and sarcasm for the audience in the film Gara Gara Warisan. Gara Gara Warisan" is a humorous family film that revolves around family issues related to inheritance. The use of satire and sarcasm was found for each character in the film Gara Gara Warisan when to convey their feelings. This study aims to understand the meaning of the language of satire and sarcasm in the film Gara-Gara Warisan by using Roland Barthes' semiotic analysis using the idea of two significant stages. This study aims to understand the meaning of the language of satire and sarcasm in the film GaraGara Warisan by using Roland Barthes' semiotic analysis using the idea of two significant stages. Through each scene, the representation of communication is in the language of satire and sarcasm towards heritage in the film GaraGara Warisan. The method used in this study was a qualitative method using Roland Barthes' semiotic analysis of denotations, connotations and myths. In this study the data collection techniques to be used are observation, documentation and interview techniques with film writer and director Gara Gara Warisan. Research results suggest that there is a use of satire and sarcasm used in the film Gara Gara Warisan. the study produced 12 tables that represent clear communication between satire and sarcasm in films and myths surrounding the use of satire and sarcasm as criticism and reproach. In addition, satire and sarcasm are also used to ridicule or denigrate others.